Analisis Isi Pesan Moral Perjuangan dan Rasa Ikhlas dalam Film “172 Days” - Arfian Suryasuciramdhan; Siti Dhifah Umairah; Sharla Setyawati; M Farhan Hidayatullah; Fauzan Azima (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
172 Days is a 2023 Indonesian drama film adapted from the novel of the same name by Nadzira Shafa. The film tells the story of Zira, a young woman who is far from religion and trapped in a free lifestyle. After experiencing a dark past, Zira decides to hijrah and live a better life. On her journey, Zira meets Ameer, a young ustaz who helps her in the hijrah process. This meeting grows seeds of love between them, and they get married. However, their marriage faces various tests and trials. This film raises the themes of hijrah, love, and marriage in an inspiring and touching way. 172 Days provides a moral message about the importance of faith and steadfastness in living life. The film also shows that true love can withstand any test.